Production of interleukins in human immunodeficiency virus-1-replicating lymph nodes. - D Emilie; M Peuchmaur; M C Maillot; M C Crevon; N Brousse; J F Delfraissy; J Dormont; P Galanaud (The Journal of Clinical Investigation, 1990)
To document the in vivo interactions occurring between the immune system and HIV replicating cells, we analyzed using in situ hybridization the production of IL-1 beta, IL-6, IL-2, and INF-gamma in eight hyperplastic lymph nodes from HIV-1 infected patients. Numerous IL-1 beta- and IL-6-producing cells associated in clusters were detected in sinuses. Few individual IL-1 beta- and IL-6-producing cells were present in interfollicular and follicular areas. IL-2- and INF-gamma-producing cells were observed in all lymph node compartments, with a selective enrichment in germinal centers. The amount and distribution of IL-1 beta, IL-6-, and IL-2-producing cells in HIV lymph nodes were not different from those found in six HIV unrelated hyperplastic lymph nodes. In contrast, a higher level of INF-gamma production was observed in HIV-1 lymph nodes. The CD8+ cells that accumulate in germinal centers of HIV lymph nodes (and not in non-HIV germinal centers) were actively involved in this INF-gamma production. INF-gamma synthesizing cells were in direct contact with cells containing HIV core antigens and HIV RNA. Thus a high INF-gamma production may characterize anti-HIV T cell immune response, potentially contributing to control of viral spreading as well as to the development of follicle lysis. Images